ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KANTOR BERSAMA SAMSAT KOTA TANGERANG PASCA PANDEMI COVID-19 - Kristanti, Kristanti (Universitas Islam Syekh-Yusuf, 2022)
This study aims to determine the factors that inluence the mandatory compliance of motorizes vehicle passengers i the joint ofice of the Tanggerang city. The study used a questionnaire tool in data collection. The data used in this study is primary data. The population used in the research are motor vehicle taxpayers who are registered at the joint office of samsat. The sampling technique used was purposive sampling with a total sample 96 responden. The data analysis technique used is analisis SPSS version 24. This study shows that the E-samsat program has no effect on motor vehicle taxpayer compliance with a significant level of 0,154 > 0,05, mobile samsat has an effective on motor vehicle tax payer compliance with value 0,543 > 0,05, and PKB whitening has a significant efecr on otor vehicle taxpaye compliance with a significant 0,569 > 0,05.